AN ECONNOMICAL STUDY OF SOME INDICATERS OF FOOD SECURITY IN IRAQ DURING THE PERID (1990-2015)/ WHEAT AS CASE STUDY - & AL-Hani, Gasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was aimed shedding light on some indicators that reflect the ability of the society to achieve an adequate degree of food security from the wheat crop. The length of the two periods of production adequacy and coverage of imports for local consumption of wheat and the stability of these periods were estimated. The period of the annual change in the rate of self-sufficiency, the per capita share and the gap between the per capita share and the need for wheat in Iraq for the period 1990-2015was estimated. It was found that the rate of self-sufficiency of the wheat crop was 54%. The annual increase in the period of production adequacy for the domestic consumption of the wheat crop was estimated at 11.5 days, or about 5.74% of the average period of production efficiency for domestic consumption. The study showed that the average period of coverage of imports for domestic consumption of wheat was estimated at 164.66 days, about 5.52 months during the study period. The period of coverage of imports for domestic consumption decreased. The annual decrease in the period of coverage of imports for domestic consumption of wheat was estimated at 0.86 days, about 0.52% of the average period of import coverage. To the lack of agricultural potential, but they are available well enough to achieve national food security and even possible to contribute to solving part of the problem of global food security, and that food security in Iraq in its current situation causes a negative impact on development to the large financial allocations to him, Other agricultural products, including the agricultural sector.